Professional Scala - Bedrytski, Aliaksandr; Bogucki, Janek; Lacava, Alessandro; Detrich, Matthew de; Neil, Benjamin (Wrox, a Wiley brand, 2016)
'Professional Scala' provides experienced programmers with a complete Scala reference and tutorial. Designed specifically to meet the needs of professionals, this guide provides everything you need to know to use Scala in professional production applications.